2021
DOI: 10.1177/17448069211037887
|View full text |Cite
|
Sign up to set email alerts
|

Spinally projecting noradrenergic neurons of the locus coeruleus display resistance to AAV2retro-mediated transduction

Abstract: Background The locus coeruleus (LC) is the principal source of noradrenaline (NA) in the central nervous system. Projection neurons in the ventral portion of the LC project to the spinal cord and are considered the main source of spinal NA. To understand the precise physiology of this pathway, it is important to have tools that allow specific genetic access to these descending projections. AAV2retro serotype vectors are a potential tool to transduce these neurons via their axon terminals in the spinal cord, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…The lumbar spinal cord receives substantial descending input from serotonergic, noradrenergic, and gabaergic populations, yet together they comprised less than three percent of cells retrogradely transduced with AAV2-retro. The relative inefficiency of AAV2-retro in serotonergic and noradrenergic cell types has been noted previously by our lab and others (Ganley et al, 2021;Tervo et al, 2016;Wang et al, 2018). The current data thus add to accumulating evidence that the tropism of AAV2-Retro favors glutamatergic neurons and points toward the importance of developing additional retrograde vectors with tropism appropriate for additional cell types.…”
Section: Implications For Injury and Diseasessupporting
confidence: 78%
See 1 more Smart Citation
“…The lumbar spinal cord receives substantial descending input from serotonergic, noradrenergic, and gabaergic populations, yet together they comprised less than three percent of cells retrogradely transduced with AAV2-retro. The relative inefficiency of AAV2-retro in serotonergic and noradrenergic cell types has been noted previously by our lab and others (Ganley et al, 2021;Tervo et al, 2016;Wang et al, 2018). The current data thus add to accumulating evidence that the tropism of AAV2-Retro favors glutamatergic neurons and points toward the importance of developing additional retrograde vectors with tropism appropriate for additional cell types.…”
Section: Implications For Injury and Diseasessupporting
confidence: 78%
“…Interestingly, nearly all clusters expressed either Slc17a6 or -7, while only three very small clusters expressed the inhibitory, serotonergic, or noradrenergic markers: these non-glutamatergic clusters comprised less than 3% of the analyzed nuclei ( Figure 2D, E ) This level of glutamatergic enrichment is likely disproportionate to brain-lumbar projection types, as inhibitory neurons may comprise more than one third of brainstem-spinal projection neurons (Holstege, 1991). One likely explanation is that the tropism of AAV2-retro favors glutamatergic neurons over others (Ganley et al, 2021; Tervo et al, 2016; Wang et al, 2018). In summary, retrograde viral labeling and FANS of produces a high purity neuron population, predominantly glutamatergic, which readily segregates into transcriptionally distinct clusters.…”
Section: Resultsmentioning
confidence: 99%
“…We spinally microinjected AAV retrograde vectors (AAVrg, 33 ) carrying floxed red-shifted cruxhalorhodopsin, Jaws 34 , fused with eGFP under pan-neuronal-specific promoter (synapsin), and a minimum of 1 week later, a second AAV9 vector encoding Cre recombinase under tyrosine hydroxylase (TH) promoter was microinjected into the relevant nuclei (A5, A6 or A7) ipsilateral to the spinal injection to restrict labelling to catecholaminergic neurons in situ . We found that this intersectional approach efficiently labels non-coerulean (A5 and A7) spinal noradrenergic projections but shows low efficiency for the coerulean system (A6) 35 ([AAVrg]: 39%, 1.1%, and 12.6% - percentage of all DBH+ neurons in the A5, A6, and A7, respectively) (Fig. 4a, b, S2a, b, c).…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence to suggest that some projections are resistant to retrograde transduction with AAV2retro vectors, and comparisons with independent tracing methods are required to demonstrate this resistance [26; 60]. To study the anatomical organization of serotonergic pathways using a non-viral method, we used Cholera toxin b subunit (CTb) retrograde tracing and compared the hindbrain labelling with our AAV2retro tracing experiments (Figure 1- figure supplement 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The AAV2retro serotype has been developed for the retrograde delivery of genetic material to projection neurons via their axon terminals in a target region [60]. Many projection neurons are found to display some resistance to transduction with these tools, for example dopaminergic neurons that project from the substantia nigra to the striatum and descending noradrenergic neurons of the locus coeruleus to the spinal cord [26; 60]. Like others, we also find that midline neurons including the NRM serotonergic neurons are less sensitive to AAV2retro-mediated transduction [65].…”
Section: Discussionmentioning
confidence: 99%